Overlay multicasting for small group application in MANETs. (18th June 2007) - Jeong, Hong-Jong; Joung, Uhjin; Kim, Dongkyun
Most MANET multicast routing protocols require intermediate nodes to maintain the multicast membership information. Efforts to reduce such an overhead proposed overlay multicast mechanisms, especially for small group. We propose the overlay small group multicast mechanism, called Shortest Path overlay Multicast (SPM) to improve the performance in terms of the distribution delay of packets and the bandwidth needed for the delivery. SPM creates the shortest path overlay tree from the paths toward each receiver which are provided by underlying routing protocols.